Approaches to blushing: context matters - Gen Eickers (Perspectiva Filosófica)
This paper offers a systematic treatment of the social and cultural context of the blush. The paper looks into how different emotion theories approach blushing and does so by differentiating between basic emotion theories, which consider contextual factors but do not make them central to understanding emotional expressions, and contextual emotion theories, which make contextual factors central to understanding emotional expressions. The paper argues that blushing might be best explained by theories that make context central to understanding emotional expression.